Kreativitas Anak Putus Sekolah di Jorong Ampang Gadang 1 Kenagarian Maek Kabupaten Lima Puluh Kota Provinsi Sumatera Barat - Khairina, Waladani; Yarni, Linda (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the phenomenon of the author's observations of several children who are less able to develop their creativity properly because children do not have the money to continue their education, knowledge in terms of creativity which is usually obtained in schools is no longer accepted by children, so that children's creativity becomes hampered. Furthermore, children who drop out of school do not have thewill to develop their creativity, children just want to stay at home and do not want to do any activities including the development of their creativity. Children prefer to have fun with their friends than to do activities that can develop their creativity. This study uses a descriptive type of qualitative approach. The results of this study are the factors that affect the creativity development of dropout children in Jorong Ampang Gadang 1 Kenagarian Maek are divided into two factors, the first is internal factors, namely physiological factors in the form of children's physical conditions, internal motivation related to the child's inner vision and external motivation in the form of support. from other people. The two external factors are family (parents), society and the media. From the results of the research conducted, some suggestions for parents are expected to be able to equip children with personal qualities that allow children to becomecreative individuals, and for the community it is expected to provide a good example for children in the development of their creativity as well as jorong Ampang Gadang 1 is expected to provide motivation to children so that children are enthusiastic in developing their creativity and for out-of-school children are expected to make the best use of time and use time with things that are useful for themselves and others.